Precipitation of fierro and sequential manganese of drain effluents - Calderón de Alvarado, Julia Marilú (2021)
Acid effluents from the leaching of sulphide minerals could be a liability that will return part of the cost of treatment when economic elements such as Fe and Mn are obtained. In this practical part of the neutralization with lime, it is precipitated as ferric hydroxides (III) and manganese (IV) hydroxides the pH must be controlled for each stage. Although the pH initially started at 2.2, an effluent has been achieved according to the standards established for its discharge or reuse. Dry hydroxides can reach very profitable levels, making the treatment sustainable and also clearing metals from the sludge that commonly goes to the tailings.